2013
DOI: 10.1002/tea.21074
|View full text |Cite
|
Sign up to set email alerts
|

Assessing students' understanding of inquiry: What do prospective science teachers notice?

Abstract: The theoretical construct of teacher noticing has allowed mathematics teacher educators to examine teacher thinking and practice by looking at the range of activities that teachers notice in the classroom. Guided by this approach to the study of teacher thinking, the central goal of this exploratory study was to identify what prospective science teachers notice when evaluating evidence of student understanding in another teacher's inquiry-based unit. Our results are based on the qualitative analysis of 43 pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…Engaging K‐12 students with authentic inquiry experiences that progressively approximate scientific practice has been a consistent and major theme in science education reforms for the past half century (Abd‐El‐Khalick et al, ). While some progress has been achieved in this regard, much remains to be desired: K‐12 science instruction largely continues to be incommensurate with how scientists conduct their practice (Anderson, ; Talanquer, Tomanek, & Novodvorsky, ). Toward achieving this goal, reforms have called for, explicitly or implicitly, a three‐step process for effecting change.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging K‐12 students with authentic inquiry experiences that progressively approximate scientific practice has been a consistent and major theme in science education reforms for the past half century (Abd‐El‐Khalick et al, ). While some progress has been achieved in this regard, much remains to be desired: K‐12 science instruction largely continues to be incommensurate with how scientists conduct their practice (Anderson, ; Talanquer, Tomanek, & Novodvorsky, ). Toward achieving this goal, reforms have called for, explicitly or implicitly, a three‐step process for effecting change.…”
Section: Discussionmentioning
confidence: 99%
“…Using a framework that delineates different features of student algebraic thinking (e.g., Manipulation of Symbols and Procedures; Reasoning with and about Representations), Walkoe analyzes how teachers' attention shifts among these different features over the course of a video club professional development experience. Similarly, Talanquer et al (2013) assess their teachers' abilities to notice specific aspects of scientific inquiry (e.g., Asking Questions and Formulating Hypotheses; Interpreting and Evaluating Evidence). Notice that this work characterizing teacher attention is domain-(and even sub-domain-) specific; researchers articulate aspects of student ideas that are disciplinarily meaningful and track whether and how teachers are paying attention to those different aspects.…”
mentioning
confidence: 99%
“…Our work revealed that teachers' selection of assessment questions is largely influenced by the perceived cognitive demand and efficacy of the task, as well as by student characteristics such as perceived ability to answer a question. More recently, we investigated what prospective science teachers notice when engaged in the evaluation of evidence of student understanding in an inquiry‐based unit (Talanquer, Tomanek, & Novodvorsky, ). Our findings suggest that prospective science teachers pay preferential attention to student performance of process skills associated with designing an investigation versus those practices related to the analysis of data and generation of conclusions.…”
mentioning
confidence: 99%